EMPIRICAL GROWTH RATE ANALYSIS OF PEARL MILLET PRODUCTION IN NIGERIA: COMPARATIVE ASSESSMENT OF POLICY REGIMES - K. SUHASINI, UMAR S. MAIADUA and (The Journal of Research, PJTSAU, 2019)
Growth of agriculture has been linked to sound and laudable agricultural policies and programmes which provide frame work, plan of actions and coordinated activities that seek to achieve self sustaining growth in all the sub-sectors of agriculture and possible realization of the structural transformation of agribusiness environment and value chains. This paper assessed the performance of pearl millet production under various policy regimes in Nigeria using time series data from 1960-61 to 2015-16. Findings from compound annual growth rate indicated that, there was a positive growth in area during period of economic diversification and structural adjustment programme (SAP). Productivity was noted to be high in period of policy of rehabilitation and reconstruction. Log quadratic function in time variable revealed that there was no acceleration in growth of pearl millet production during the studied periods thus, underscoring the policy regimes especially SAP period which recorded decelerated growth. The study advocated yield growth inducing policies in terms of credit and farm input support, enhancement of pearl millet value chain within the prism of agribusiness and infrastructural support.